Neural correlates of body and face perception following bilateral destruction of the primary visual cortices - Van den Stock, Jan; Tamietto, Marco; Zhan, Minye; Heinecke, Armin; Hervais-Adelman, Alexis G.; Legrand, Lore; Pegna, Alan J.; de Gelder, Beatrice (Frontiers in Behavioral Neuroscience, 2014)
Non-conscious visual processing of different object categories was investigated in a rare patient with bilateral destruction of the visual cortex (V1) and clinical blindness over the entire visual field. Images of biological and non-biological object categories were presented consisting of human bodies, faces, butterflies, cars, and scrambles. Behaviorally, only the body shape induced higher perceptual sensitivity, as revealed by signal detection analysis. Passive exposure to bodies and faces activated amygdala and superior temporal sulcus. In addition, bodies also activated the extrastriate body area, insula, orbitofrontal cortex (OFC) and cerebellum. The results show that following bilateral damage to the primary visual cortex and ensuing complete cortical blindness, the human visual system is able to process categorical properties of human body shapes. This residual vision may be based on V1-independent input to body-selective areas along the ventral stream, in concert with areas involved in the representation of bodily states, like insula, OFC and cerebellum.